Project based learning for chi̇ldren with mild mental disabilities - (:unkn) unknown (My University, 2007)
The aim of this investigation was to determine the effectiveness of a project-based learning program delivered to children with mild mental disabilities. The 7 children (4 girls and 3 boys) selected for this experimental study were from an elementary school and attending a special class. The theme of the project was Patisserie. At posttest the group performed significantly better than at pretest in general and in all subtests (point to the patisserie, point to the foods/drinks, point to the workers, point to the things at the patisserie, what we give to the waiter before leaving and proper behavior at the patisserie). Results showed the importance of project-based learning for the children.